PENYEMPURNAAN PENGENDALIAN TERPADU PENYAKIT TUNGRO DENGAN STRATEGI MENGHIDARI INFEKSI DAN PERGILIRAN VARIETAS TAHAN - Burhanuddin, I. Nyoman Widiarta, dan Andi Hasanuddin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2006)
Refining integrated rice tungro disease management based on escaped strategy and varieties rotation. Rice tungro virus transmitted mainly by green leafhopper, N. virescens, infected rice in central rice production in Indonesia. Tungro epidemic in South Sulawesi were succesfully controlled by integrating appropriate planting time and rotation of green leafhopper resistant varieties since 1973. Tungro was reported in 1998 after climate anomaly, caused by El-Nino and La-Nina. Pattern of green leafhopper population fluctuation and tungro disease incidence and green leafhopper adaptation to green leafhopper resistance variety were evaluated. The results showed that the fluctuation pattern of green leafhopper population in Lanrang which represents of areas in Eastern Coarse of South Sulawesi has changed. Green leafhopper colonies from endemic area in South Sulawesi were almost all well adapted to 4 groups of green leafhopper resistance varieties. Therefore it was suggested to adjust planting date and recommended to plant tungro virus resistance variety instead of green leafhopper resistance varieties.